Increasing maternal knowledge through counseling on the consumption of risky foods in children aged 2-10 years - Alam, Syamsul; Ansyar, Dian Ihwana; Junita, Syamsurya; Putri, Ayuni; Magfirah, Fifi (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
Nutritional status of thin, short, and fat that is high enough indicates food intake that is still unbalanced. Children's food intake is influenced by diet, when food supply, physical activity, and snack habits. One of the efforts to reduce the consumption of risky foods (instant snacks) is the implementation of the IEC program (communication, education, and information). The type of research used is observational with a descriptive approach and the sampling techniques used are simple random sampling and purposive sampling. The entire study population was mothers living in Bontona hamlet, Kanreapia village, Tombolo Pao District, Gowa Regency, totalling 32 respondents. In the implementation of the program, the results of increasing maternal knowledge were obtained after counselling activities on excessive consumption of risky foods (instant snacks) in children aged 2-10 years. Through this activity, it is hoped that mothers can practice the knowledge they have in parenting, especially the practice of providing nutritious food